Debt to fececam and profitability of agricultural farms in benin - AIFA, Emile (Edelweiss Applied Science and Technology, 2024)
In Benin where microfinance as a community development tool has experienced rapid emergence in recent decades, microcredit is seen as the best financial alternative to allow the poorest to access capital through support and support for local structures . It is thanks to this situation that the Fécécam network (Fédération des Caisses d’Epargne et de Crédit Agricole Mutuel), the oldest and the most important in terms of membership at the national level, was restructured to allow several farms farmers to benefit from microcredits. But, after a few years of activities with this institution , several farmers suffered enormous losses, thus causing unpaid bills in the network’s portfolio . The main objective of this study is to report on the factors which determine the profitability of said microcredit on farms in Benin, even if it means facilitating the repayment of microcredits received . Thus, from samples constituted for the sectors: cotton, soya, corn and cassava, we have shown, using the generalized method of moments, that debt negatively affects the profitability of most sectors, at the same time, linear and non-linear manner. To this end, in order to ensure the effectiveness of the credits obtained, it is necessary to review the structure of the credits, their granting procedures and the amounts allocated, while ensuring that the tax charges are not very high.